Wearable cardioverter-defibrillator as bridging to ICD in pediatric hypertrophic cardiomyopathy with myocardial bridging - a case report - Stefan Kurath-Koller; Hannes Sallmon; Daniel Scherr; Egbert Bisping; Ante Burmas; Igor Knez; Martin Koestenberger (BMC, 2020)
Abstract Background There is only limited experience with wearable cardioverter-defibrillators (WCD) in pediatric patients. We report on the successful application of a WCD in an adolescent patient with hypertrophic cardiomyopathy and myocardial bridging. Case presentation A 15-year-old girl presented with a history of recurrent syncope, dyspnea, and vertigo with exercise. Diagnostic work-up revealed non-obstructive hypertrophic cardiomyopathy and signs of myocardial ischemia with exercise. Given this high-risk constellation, the patient was scheduled for prophylactic implantation of an implantable cardioverter-defibrillator (ICD). One month after initial presentation and days prior to the planned ICD implantation, the patient collapsed during an episode of sustained ventricular tachycardia (VT) while running. VT was terminated by WCD shock delivery. Following this event, computerized tomography scan revealed myocardial bridging of the left anterior descending coronary artery causing a 90% stenosis in systole. After coronary surgery, life threatening arrhythmias have not recurred, but due to progressive heart failure, the patient underwent successful heart transplantation after 2 years. Conclusions The reported case highlights the importance and applicability of WCDs and the potentially malign nature of myocardial bridging in pediatric high-risk patients.